2015
DOI: 10.1007/s00382-015-2762-3
|View full text |Cite
|
Sign up to set email alerts
|

Interannual-decadal variability of wintertime mixed layer depths in the North Pacific detected by an ensemble of ocean syntheses

Abstract: central mode water formation region in phase opposition with those in the eastern subtropics and the central Alaskan Gyre. This first EOF mode is highly correlated with the Pacific decadal oscillation index on both the interannual and decadal time scales. The second leading EOF mode represents the MLD variability in the subtropical mode water (STMW) formation region and has a good correlation with the wintertime West Pacific (WP) index with time lag of 3 years, suggesting the importance of the oceanic dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The subsurface NPESTMW originates from a deep mixed layer in its formation region over the late winter, and this region can therefore be inferred from surface conditions. February and March are selected as the late winter since the MLDs in these months are both quite deep (Toyoda et al, , ). In addition, the distribution of a deep mixed layer varies from year to year, and the late winter climatology may fail to catch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsurface NPESTMW originates from a deep mixed layer in its formation region over the late winter, and this region can therefore be inferred from surface conditions. February and March are selected as the late winter since the MLDs in these months are both quite deep (Toyoda et al, , ). In addition, the distribution of a deep mixed layer varies from year to year, and the late winter climatology may fail to catch.…”
Section: Methodsmentioning
confidence: 99%
“…The PDO index is defined as time series of the first empirical orthogonal function of SST north of 20°N in the Pacific. A recent study by Toyoda et al () suggested that the wintertime mixed layer depth (MLD) anomalies in the NPESTMW formation region also negatively correlate with the PDO index on both interannual and decadal time scales.…”
Section: Introductionmentioning
confidence: 99%
“…The ORA (Ocean Reanalysis) Intercomparison Project was initiated under CLIVAR GSOP and GODAE‐Oceanview and has produced a series of papers examining global ocean reanalyses and focusing on different aspects of the ocean state (e.g., steric sea level, air‐sea fluxes, ocean heat, and salt content among others). These were then brought together in a special issue of Climate Dynamics (Balmaseda et al, ; Chevallier et al, ; Karspeck et al, ; Palmer et al, ; Shi et al, ; Storto et al, ; Masina et al, ; Toyoda, Fujii, Kuragano, Kamachi, et al, ; Toyoda, Fujii, Kuragano, Kosugi, et al, ; Tietsche et al, ; Valdivieso et al, ). A further paper on the polar oceans was later added (Uotila et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the monthly MLD anomalies in the bloom and prebloom months. Note that the reanalysis ensemble used to determine the mean MLD field well reproduced both the seasonal MLD cycle and interannual variability by effectively synthesizing oceanic and atmospheric (via surface forcing from atmospheric reanalyses) observations and dynamical models, with the model errors canceling out through ensemble averaging [ Toyoda et al ., a, b]. Positive MLD anomalies were seen in the last two months before the blooms (Figure ).…”
Section: Physical Conditions Associated With Bloomsmentioning
confidence: 96%